Nurturing Infants Exploring Ayurveda’s Holistic Approach to Care - Kumar, Archit; Sharma, Brahm Dutt; Ojha , Nisha K (International Research Journal of Ayurveda & Yoga, 2024)
Abstract Introduction – Ayurveda encompasses a wide range of practices within pediatric care especially plays a pivotal role in nurturing infants by offering safe and effective approaches not only for disease treatment but also for maintaining overall health in this span of age. Acharyas offered their insights on all aspects of newborn and infant care, spanning from birth until the newborn’s complete stability. Methods - This study was completed by gathering the knowledge from classical Ayurvedic literature, research articles, guidelines, and PubMed and MedLine databases. Results and Discussion- This study investigates traditional Ayurvedic methods for infant care placing particular attention on evaluating the safety and effectiveness of these practices within the framework of neonatal and infant healthcare upto the age of one year. Conclusion –Kaumarbhritya is seen as the first direct assistance provided by the science of Ayurveda to a newborn upon his debut in this new world, directing him towards a healthy lifestyle in the future and bringing out the finest version of himself. This paper offers an overview of the literary contributions and historical traditional medical practices of healthcare in the domain of Balachikitsa mainly of neonatal and infancy period.The goal is to underscore the significance of research grounded in evidence and its integration into hidden principles concerning neonatal and infant issues described in Ayurveda.